ANALISIS KELAYAKAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) SEPATU DAN SANDAL DI BOGOR - Olivia Venessa Nainggolan (Jurnal Bina Akuntansi, 2018)
Feasibility Study for Shoes and Sandal Micro Business in Bogor is very important to be conducted. The purpose of this feasibility study is to measure cost and benefit that might be beneficial for every stakeholder especially in rural area. Pasir Eurih Village has been knowned as one of shoes and sandal producer. Long history and many craftman there has been made shoes and sandal for generation. Their knowledge and skill has been passed from generation to generation and create microbusiness and become main economics activity for villager there. Unfortunately there is question that, why such old microbusiness never grow and expand more? In order to answer this question researcher conducted some feasibility study regarding this matter. Researcher wants to search the root of the problem why this microbusiness from Pasir Eurih Village not grow and expand. In this research, researcher conducted feasibility study base on two main aspect of feasibility study. First aspect is non financial aspect of the business which is management, business entities, infrastructure, and some SWOT analysis base on current situation. Second aspect is financial aspect which is NPV, IRR, Profitability Index, and Payback Period. Finding in this research is base on the market, internal competency Pasir Eurih has GOOD feasibility but unfortunately still not manageable with good corporate governance. Lack of leadership and there is no certain business entities that could coordinate this microbusiness cause major delay of its expansion. Researcher purposes that in first step of development, Pasir Eurih could start to organize their internal stakeholder under cooperation business entities (KOPERASI). Pasir Eurih already has KOPERASI but found by researcher failed to be functioned. In order to create competitive product and expand their internal stakeholder need to be trained and develop untuk the best business entities (which is in researcher opinion is KOPERASI). Finally, it is human development that is urgent issued that found by researcher in this topic. Government and some professional business should be together developed rural area in order to achive competitive nation and product.